2019
DOI: 10.1088/1742-6596/1233/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Physics Learning Devices based on Guided Inquiry with Experiment to Improve Students’ Creativity

Abstract: In this study, we have developed physics learning devices based on guided inquiry with experiments to improve students’ creativity. Research and development are carried out in several stages starting with preliminary studies to testing. Experts then validate learning tools that have been developed before being implemented to determine their effectiveness in increasing creativity. Validity data was obtained from the appraisal sheet for the appraisal of learning devices that are assessed by experts. The effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 8 publications
0
7
0
4
Order By: Relevance
“…Husein et al (2019) suggested that the use of interactive multimedia had a positive effect on the conceptual understanding of thermodynamics. Along with that, Wahyuni et al (2019) added that there was an increase in creativity by applying interactive multimedia rather than conventional learning. Gunawan & Liliasari (2012) also found that the use of a virtual lab of physics could improve critical thinking dispositions.…”
Section: Introductionmentioning
confidence: 99%
“…Husein et al (2019) suggested that the use of interactive multimedia had a positive effect on the conceptual understanding of thermodynamics. Along with that, Wahyuni et al (2019) added that there was an increase in creativity by applying interactive multimedia rather than conventional learning. Gunawan & Liliasari (2012) also found that the use of a virtual lab of physics could improve critical thinking dispositions.…”
Section: Introductionmentioning
confidence: 99%
“…A literatura tem apontado que o uso de abordagens baseadas na integração entre teoria e experimento no ensino em Física [1][2][3] e que incentivem uma postura ativa dos estudantes ao longo da construção de seu conhecimento [2][3][4][5] favorecem o desenvolvimento de capacidades de generalização [1], reflexão [1,5] e autonomia [1,2]. Em tais abordagens, procura-se fazer com que conceitos, fenômenos, formalismo matemático e prática (laboratorial e computacional) sejam estudados conjuntamente [1].…”
Section: Motivação E Históricounclassified
“…Kreativitas merupakan kemampuan individu dalam pemikiran berbeda, pemikiran yang produktif, mampu menghasilkan karya, dan mampu dalam menggabungkan berbagai informasi sehingga menciptakan kombinasi dan hasilnya tidak selalu baru (Astutik, 2020;Gunawan, 2018;Tan, 2015). Di dalam pendidikan kreativitas kurang diperhatikan, seharusnya setiap siswa berpotensi untuk mengembangkan kreativitas sehingga mereka mampu menjawab tantangan di era 21 (Wahyuni, 2019).…”
Section: Pendahuluanunclassified